Air temperature at a height of 2 m in Kozia Dolina Valley (Tatra Mts.) - Stanisław Kędzia (PANGAEA, 2025)
The climate of a high-altitude postglacial cirque, such as Kozia Dolinka, is conducive to the occurrence of permafrost. Both the depth of permafrost and the area it covers, as well as the presence of year-round snow patches, can serve as indicators for assessing the impact of global warming on the climate of mountains, including the Tatras. With few meteorological stations to survey the remote and inaccessible high-altitude areas of the Tatra Mountains, any research must rely on measurements spanning limited time periods. Against this background, the 5-year series of temperature measurements from the Kozia Dolinka cirque obtained by the Institute of Geography and Spatial Organization of the Polish Academy of Sciences (IGiPZ PAN) can be used to analyze air temperature patterns on concave and convex terrain forms in the alpine climate zone if compared to the results of measurements from stations of the State Hydrological and Meteorological Service located nearby, i.e. the Kasprowy Wierch High Mountain Meteorological Observatory and the Hala Gąsienicowa Nival Research Station of the Institute of Meteorology and Water Management, National Research Institute (IMGW-PIB). This study confirms that there is a relationship between air temperature and the formation and duration of snow cover on concave and convex terrain forms. It also reveals a hitherto unknown fact that concave terrain forms, i.e. postglacial cirques, of the alpine zone have milder thermal conditions in winter than convex terrain forms. The analyses highlight the need for further, more detailed research using modern automated meteorological stations.